Outpatient Video Visits During the COVID-19 Pandemic: Cross-Sectional Survey Study of Patients' Experiences and Characteristics - Stefanie C van den Bosch; Demi Van Dalen; Marjan Meinders; Harry van Goor; Stefaan Bergé; Martijn Stommel; Sandra van Dulmen (JMIR Publications, 2024)
BackgroundDuring the first lockdown of the COVID-19 pandemic, an exponential increase in video consultations replacing in-person outpatient visits was observed in hospitals. Insight into patients' experiences with this type of consultation is helpful for a broad, sustainable, and patient-centered implementation of video consultation. ObjectiveThis study aims to examine patients' experiences with video consultation during the COVID-19 pandemic and identify discriminative patient and consultation characteristics to determine when video consultation is most feasible. MethodsA cross-sectional survey study was conducted. Patients aged ≥18 years and scheduled for a video consultation at the outpatient clinic of a Dutch university medical center from August 2020 to December 2020 for all medical specialties were eligible. Patients' experiences were explored through a study-specific survey using descriptive quantitative statistics. Open-ended questions were qualitatively analyzed and thematically categorized into appreciated aspects and aspects for improvement. Discriminative patient and consultation characteristics were identified using 3 distinctive survey items. Characteristics of patients who scored and those who did not score all 3 items positively were analyzed using binary logistic regression. ResultsA total of 1054 patients were included in the analysis. Most patients (964/1054, 91.46%) were satisfied with their video consultation, with a mean overall grade of 8.6 (SD 1.3) of 10. In the qualitative analyses, 70.02% (738/1054) of the patients cited aspects they appreciated and 44.97% (474/1054) mentioned aspects for improvement during their consultation. Patients with better self-rated health reported a positive evaluation significantly more often (P=.001), which also held true for other medical specialties (vs surgical and nonsurgical specialties; P<.001). ConclusionsVideo consultation was perceived as highly satisfactory by patients during the COVID-19 pandemic, with the best experience reported by healthy participants and those undergoing their first consultation. Appreciated aspects are mainly at the individual professional level, organizational level, and innovation level itself. The aspects that were mentioned for improvement can be changed for the better.